Pelatihan Instalasi Sistem Operasi Server Berbasis linux Pada Siswa SMK Yapdi Bandar Pulau - Irianto Irianto; Afrisawati Afrisawati; Sahren Sahren (Jurnal IPTEK Bagi Masyarakat, 2021)
This community service activity aims to provide training to students of SMK Yapdi Bandar Pulau on Installing a Linux Server Operating System based on CentOS 7. Submission of material is carried out theoretically and directly in practice in installing a Linux server operating system. Several important points were conveyed theoretically and practically in this activity, such as an explanation of a Linux-based server or network operating system. Then in practice, the participants were guided directly to perform the installation and basic configuration for this server operating system. Materials given to participants up to 90% of the knowledge about the Linux server operating system and how to install it. Based on the results of the discussions carried out in the form of question and answer discussions and direct practice, the understanding of the participants reached 92% for the level of understanding of the material provided.